H∞ Robust Tracking Control of Stochastic T-S Fuzzy Systems with Poisson Jumps. (2nd October 2018) - Lin, Xiangyun; Zhang, Weihai; Chen, Bor-Sen
Abstract : A robust adaptive H ∞ tracking control design for nonlinear stochastic systems with both Brownian motion and Poisson jumps is proposed, which is based on Takagi–Sugeno (T-S) type fuzzy techniques. Because the state of to-be-controlled systems cannot be known exactly, to overcome this difficulty, the state estimation systems and error estimation systems are introduced to obtain an augmented system. By using the fuzzy systems to approximate the nonlinear systems, an adaptive fuzzy control is employed to achieve the desired H ∞ tracking performance for stochastic systems with exogenous disturbance. A simulation example is presented to illustrate the tracking performance of the proposed design method.